Development of a RELAP5 model for the thermo-hydraulic characteristics simulation of the helically coiled tubes. (April 2021) - Xu, Ziyi; Liu, Maolong; Xiao, Yao; Gu, Hanyang
Highlights: A heat transfer coefficient and friction factor model for helical tubes is proposed. The model for helical tubes is added to the RELAP5 code. The model accurately predicts the heat transfer coefficient and pressure drop. The model accurately predicts the flow instability thresholds in parallel tubes. Abstract: In helically coiled tubes, the geometry induced centrifugal forces exert the fluid enhancement upon the heat transfer and pressure drop. Hence, it is essential to develop a thermo-hydraulic model for helical tubes. This paper reviewed many previous studies and summarized the published correlations. The heat transfer coefficient and friction factor models were respectively developed by evaluating the applicability of these correlations in various operating parameters. Then the developed models were applied in RELAP5 code to simulate the flow and heat transfer behavior in a helical tube under steady-state conditions, and it was found that the simulation results were in good agreement with the experimental data. The modified code was also used to simulate flow instability phenomena in parallel helical tubes. And the results showed the modified code can accurately predict the oscillation periods and the instability thresholds of density-wave oscillations in helical tubes within a wide range of operating parameters.